A QR code based tracing method for fresh pork quality in cold chain. (25th March 2018) - Peng, Yaoqi; Zhang, Lingxian; Song, Zhixing; Yan, Jin; Li, Xinxing; Li, Zhenbo
Abstract: Fresh pork is a meat that many people choose to eat in daily lives, and it is becoming more important to devise a method for ensuring the quality and safety of fresh pork. Combined with the meat quality of the cold chain and the environmental information collection program, this study presents a QR code based tracing method for a quality tracing system. This method includes a correction recognition test for the final design of the QR code. The results show that QR code can store large amounts of traceability information, with strong error correction capability, and can provide a great advantage in scanning recognition. In the process of consumption, consumers can easily obtain fresh pork quality information by scanning the QR code with a mobile phone, rather than having to choose a piece of meat to purchase based only on a visual observation of the meat. Practical applications: In this study, the design of the temperature acquisition scheme was verified in SMEs (small and medium enterprises), the results show that the data transmission is stable. The generated QR codes were tested in some supermarkets, have strong error correction capability, and can meet the retroactive requirements. According to this research, when the damage to the traceability barcode is beyond the range of 30% before the barcode enters circulation, the barcode needs to be reprinted.